Specific Binding and Uptake of 131I-MIBG and 111In-Octreotide in Metastatic Paraganglioma – Tools for Choice of Radionuclide Therapy - Spetz, J.; Dalmo, J.; Nilsson, O.; Wängberg, B.; Ahlman, H.; Forssell-Aronsson, E. (Hormone and Metabolic Research, 2012)
Tumor-specific uptake of the radiolabeled norepinephrine analogue meta-iodobenzylguanidine via norepinephrine transporter or radiolabeled somatostatin analogues octreotide/octreotate via somatostatin receptors offers possibilities to diagnose and treat metastatic pheochromocytoma/paraganglioma. High uptake of 123I-meta-iodobenzylguanidine is dependent on high expression of vesicular monoamine transporters responsible for mediating uptake of biogenic amines into dense core granules. A patient with metastatic paraganglioma (liver and bone metastases) underwent surgical removal of the primary after injection of 131I-meta-iodobenzylguanidine and 111In-octreotide. Radioactivity was determined in biopsies from tumor and normal tissue biopsies. The tumor/blood concentration value was high: 180 for 131I-meta-iodobenzylguanidine 3 h after injection and 590 for 111In-octreotide 27 h after injection. Studies of primary tumor cell cultures demonstrated increased cell membrane binding and internalization over time for 131I-meta-iodobenzylguanidine. The vesicular monoamine transporter antagonist reserpine and the norepinephrine transporter inhibitor clomipramine reduced internalization by 90% and 70%, respectively, after 46 h of incubation. The results demonstrated increased cell membrane binding and internalization over time also for 111In-octreotide. Internalization was highest for a low concentration of 111In-octreotide. Excess of octreotide reduced internalization of 111In-octreotide with 75% after 46 h of incubation. In conclusion, uptake and tumor/blood concentration values of radiolabeled meta-iodobenzylguanidine and somatostatin analogues can be determined for metastatic pheochromocytoma/paraganglioma to evaluate the possibility to use one or both agents for therapy. For this patient, the high tumor/blood values clearly demonstrated that therapy using both radiopharmaceuticals would be most beneficial. In vitro studies verified specific cell-membrane binding and internalization in tumor cells of both radiopharmaceuticals.
Keywords: norepinephrine transporter; VMAT; clomipramine; reserpine; somatostatin receptors; octreotate